A new variation of modern prejudice: young Korean men's anti-feminism and male-victim ideology - Jung, Han Wool (Frontiers in Psychology, 2023)
In South Korea, anti-feminism is now rapidly spreading online among young men, who have started to identify themselves as a social minority or “victims” of female power. Despite its ramifications, theoretically, anti-feminism is indistinct from the racism and sexism of White men that emerged more than half a century ago. In view of this, it shares the same root as typical modern racism or sexism, although it appears to be a novel phenomenon. Such a hypothesis was buttressed by quantifying the attitudes of anti-feminists toward various outgroups based on the transference of prejudice theory. Moreover, the subtle sexist undertones hidden in their arguments have been discussed using various psychological theories and empirical data/statistics. Additionally, various potential factors that may shape or accelerate their attitudes or behaviors have been discussed on the basis of the threat-defense theory. Through comprehensive literature review based on this theory, this study proposes the features related to Korean anti-feminism, encompassing behavioral/situational (overindulging violent or degrading Internet contents, verbal aggression), relational/epistemic (ostracism, attachment insecurity, pseudo-rationalism), and group-level (provocative interactions, polarization) attributes, some of which may also influence groups other than young men and ingrain or exacerbate the extreme ideologies of other groups, including young women. Scrutinizing Korean online anti-feminism and male-victim ideology may improve our understanding of the psychological origins of various social extremities or radical ideologies beyond cultural barriers.